Prevalence and Associated Factors of Chronic Obstructive Pulmonary Disease Among Adults in Neno District, Malawi: A Cross-Sectional Analytical Study [Letter] - Fikri E (International Journal of COPD, 2024)
Elanda Fikri1,2 1Department of Environmental Health, Poltekkes Kemenkes Bandung, Bandung, Indonesia; 2Center of Excellence on Utilization of Local Material for Health Improvement, Bandung Health Polytechnic, Bandung, IndonesiaCorrespondence: Elanda Fikri, Department of Environmental Health, Poltekkes Kemenkes Bandung, Jl.Pajajaran 56, Bandung, Jawa Barat, Indonesia, Email elandafikri@yahoo.com